Auditor Competence and Independence in Fraud Detection: The Mediating Role of Audit Technology - Nailil Farrooh; Muh. Syahru Ramadhan; Fahrul Mauzu (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the direct effects of auditor competence and auditor independence on fraud detection and to analyze the mediating role of audit technology at the Dompu Regency Inspectorate. Research Method: This study employed a quantitative approach using primary data collected through questionnaires. The research sample consisted of 60 active auditors and Government Affairs Supervisory Officials (P2UPD) with at least one year of audit experience at the Inspectorate of Dompu Regency, West Nusa Tenggara. The variables examined include auditor competence, auditor independence, audit technology, and fraud detection. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Results and Discussion: The findings show that auditor competence and audit technology have significant positive effects on fraud detection. However, auditor independence does not directly affect fraud detection. Auditor competence and independence significantly enhance the use of audit technology. Furthermore, audit technology significantly mediates the effects of both auditor competence and auditor independence on fraud detection. Implications: These findings suggest that local governments should strengthen digital audit infrastructure to improve fraud detection and regional financial accountability. Originality: This study contributes by positioning audit technology as a mediating mechanism that links auditor competence and independence to fraud detection in the context of a local government inspectorate.